(untitled) (Bangladesh Journal of Animal Science, 2012)
The study was conducted to study the effects of genotype and age of hen and hatching season on hatchability of egg. Hatching eggs were collected from hens having three genotypes viz. White Leghorn (WLH), Rhode Island Red (RIR) and Fayoumi covering three age groups (28 to 40, 41 to 60 and 61 weeks & above) at winter, monsoon and summer seasons. The study revealed that the highest (P<0.05) average hatchability was observed in winter (78.62%) followed by monsoon (76.70%) and summer (75.79%). Among different genotypes the highest (P<0.001) hatchability was found in Fayoumi (78.34%) followed by White Leghorn (76.48%) and Rhode Island Red (74.59%). Considering the age of hen, highest (P<0.05) hatchability was found in the age group between 41 to 60 weeks (77.99%) followed by 61 weeks and above (76.49%) and 28 to 40 weeks (75.71%) of age. From the findings it can be concluded that the winter season was suitable for hatching of eggs and the performance of Fayoumi hen was better in terms of hatchability of egg. On the other hand, the age of hen between 41 to 60 weeks was better for producing hatching eggs. DOI: http://dx.doi.org/10.3329/bjas.v37i1.9863 BJAS 2008; 37(1): 17-22